ASP.NET core recipes : a problem-solution approach - Ciliberti, John (Apress, 2017)
Quickly find solutions to common web development problems. Content is presented in the popular problem-solution format. Look up the problem that you want to solve. Read the solution. Apply the solution directly in your own code. Problem solved! ASP.NET Core Recipes is a practical guide for developers creating modern web applications, cutting through the complexities of ASP.NET, jQuery, React, and HTML5 to provide straightforward solutions to common web development problems using proven methods based on best practices. The problem-solution approach gets you in, out, and back to work quickly while deepening your understanding of the underlying platform and how to develop with it. Author John Ciliberti guides you through the MVC framework and development tools, presenting typical challenges, along with code solutions and clear, concise explanations, to accelerate application development. Solve problems immediately by pasting in code from the recipes, or put multiple recipe solutions together to overcome challenging development obstacles. What You'll Learn Take advantage of MVC's streamlined syntax Discover how to take full control over HTML Develop a simple API for creating RESTful web services Understand test-driven development Migrate a project from ASP.NET web forms to Core MVC, including recipes for converting DataGrids, Forms, Web Parts, Master Pages, and navigation controls Use Core MVC in combination with popular JavaScript libraries, including jQuery, React, Bootstrap, and more Write unit tests for your MVC controllers, views, custom filters, and HTML helpers Utilize the latest features in Visual Studio 2017 to accelerate your Core MVC projects Identify performance bottlenecks in your MVC application.